East-West cranial differentiation in pre-Columbian populations from Central and North America - Pucciarelli, Hector Mario (2008)
In a recent study we found that crania from South Amerindian populations on each side of the Andes differ significantly in terms of craniofacial shape. Western populations formed one morphological group, distributed continuously over 14,000 km from the Fuegian archipelago (southern Chile) to the Zulia region (northwestern Venezuela). Easterners formed another group, distributed from the Atlantic Coast up to the eastern foothills of the Andes. This differentiation is further supported by several genetic studies, and indirectly by ecological and archaeological studies. Some authors suggest that this dual biological pattern is consistent with differential rates of gene flow and genetic drift operating on both sides of the Cordillera due to historical reasons. Here we show that such East-West patterning is also observable in North America. We suggest that the "ecological zones model" proposed by Dixon, explaining the spread of the early Americans along a Pacific dispersal corridor, combined with the evolution of different population dynamics in both regions, is the most parsimonious mechanism to explain the observed patterns of within- and between-group craniofacial variability.